PRODUKTIVITAS TENAGA KERJA PADA BEBERAPA KILANG KAYU LAPIS DI SUMATERA - Akub J Abdurachman; Sylviani Sylviani (Jurnal Penelitian Hasil Hutan, 1987)
Plywood production can be increased by improving factory quality, work organization system, processing method, and by increasing the skill of the operators and other activities supporting labour productivity.Previous works indicated that low productivity of labour in plywood mill in Indonesia was mainly due to the low levels of education, skill and experiences of operators. This study is intended to obtain accurate data concerning this problem.The survey was conducted in several plywood industries in Sumatera in 1985 and revealed the following results:Average actual production of plywood mills is lower than the design production capacity.  The average ratio of actual production capacity is as low as 0.422.The productivity of employees varies between mills, especially for Managers. Managers productivity ranges from 45.2 to 242 cum/man/month (standard error 93.5 cum/man/month); administrative staff productivity 14.1-38.2 cum/man/month (standard error 9,6 cum/man/month);and operators:1.7-5.9 cum/man/month  (standard error 1.5 cum/man/month).Waging system in term of payment (monthly or others) and the amount of salary does not effect the productivity levels.